Original paperIodine-125 prostate seed brachytherapy in renal transplant recipients: an analysis of oncological outcomes and toxicity profile - Beydoun, Nadine; Bucci, Joseph; Malouf, David (Journal of Contemporary Brachytherapy, 2014)
Purpose : Prostate cancer is among the most common non-cutaneous neoplasms affecting renal transplant recipients (RTRs). Available treatments including radical prostatectomy and external beam radiotherapy carry a risk of damage to the transplanted kidney, ureters, or bladder. We assessed the safety and efficacy of Iodine-125 ( 125 I) prostate seed brachytherapy as an alternative to surgery and radiotherapy in these individuals. Material and methods: We retrospectively reviewed our brachytherapy database to identify patients with a prior history of renal transplantation, who had undergone seed implantation for localized prostate cancer. Long term PSA control and treatment related toxicity, including graft dysfunction, urinary, rectal, and sexual complications, were assessed and compared with published outcomes for surgery and external beam radiotherapy. Results: Of 1054 patients treated with permanent seed implantation from 2002-2012, we identified four who had a prior history of renal transplantation. Mean time from renal transplantation to prostate cancer diagnosis was 13 years. Mean follow-up after seed implantation was 44 months (range 12-60 months). All four patients remain free of PSA progression. No peri-operative complications were experienced following seed implantation, and all four patients continued to have normal graft function. Long term urinary and rectal function scores were comparable to reported outcomes for seed brachytherapy in the non-transplant population. Conclusions : 125 I prostate seed brachytherapy is associated with high rates of biochemical control and minimal toxicity to the renal graft in RTRs. This treatment should be considered as an alternative to surgery in managing RTRs with localized prostate cancer.